Cinco de Mayo 1991 - Art Show (and Other Events) - Castellano, Alcario:::creator::::::::::::
Video and transcripts of the 1991 Cinco de Mayo Art Show. Also included is a home video (21:32). Part of an interview (26:00). And the San Jose American GI Forum Fiestas Patrias el Centro de Nuestra Cultura (30:00).